Multiple Vascular Variations in a Single Cadaver: A Case Report - Aarathi Venunadhan, Zameera Banu, S. Danesh, S. Bindhu* (Recent Research in Science and Technology, 2010)
A sound knowledge of variations of blood vessels is important during operative, diagnostic and endovascular procedures in the abdomen and pelvis. Three variations were found during routine dissection in an approximately 55yr old male cadaver.Â Three arterial variations are described - presence of right accessory renal artery arising from the abdominal aorta, the testicular artery arising from the accessory renal artery and the obturator artery arising from the posterior division of internal iliac artery. These observations have implications for abdominal and pelvic surgeons and are of academic interest to anatomists. Surgeons dealing with kidney transplantation and obturator hernia need to be aware of these observations.